Chemical and physical composition of household wastes from selected peri-urban areas of Harare - Mhindu, R.L.; Ngorima, E.; Wuta, M. (Midlands State University, 2015)
We studied the physical and chemical characteristics of household wastes generated in three peri urban areas bordering the city of Harare in Zimbabwe. Month-long waste surveys involving 252 peri-urban households were conducted during a predominantly wet season and also during the dry season. The objective of the study was to determine waste composition and waste generation rates in target areas. Across all sites, weekly waste generation rates were significantly different for the peri-urban sites studied, being greater during the wet season than during the dry season. Waste generation rates ranged from 4.8 -2.7kg/household/week in the dry season and from 13.6kg to 7.2kg/household per week in the wet season. In both surveys waste components were predominantly organic and non-compostable materials accounted for less than 30% of the waste spectrum. Nitrogen, calcium and phosphorus were the most dominant nutrient elements present in wastes. There was minimal variation in content of essential nutrient elements across sites. Lignin content was low and also varied minimally across sites. Wastes had an average C/N ratio of 30 and were considered to be suitable for composting without the use of any additives.